The contribution of tourism to the Croatian economy : an IO approach - Ivandić, Neven (Array, 2018)
In order to understand the contribution of tourism to the economy and the effects of possible structural changes during the tourism boom that Croatia is currently facing, the article focuses on the place and role of tourism in the Croatian economy and its impact on the output of the most relevant industries. The aim of the paper is to estimate the contribution of tourism to the gross domestic product of Croatia and to measure the multiplicative effects of tourism consumption on the different industries of the economy during a nine year period, based on a specific methodological framework, which integrates tourism satellite and input-output models in three different years. The analysis has provided an approximation of the total tourist industry contribution to the national economy, ranging from 14.2 to 16.3 percent of the gross value added of the whole of the economy. It concludes that tourism consumption has a positive effect on both tourism and non-tourism products and activities. Improvement of the quality of the research within the input-output framework requires the process of the fractionalization of input-output tables but also a more precise extraction of activities characteristic of tourism than there has previously been.